Owoc zatrutego drzewa? Situation testing jako dowód w sprawach o dyskryminację: [Fruit of the poisonous tree? Situation testing as a proof in discrimination cases] (Studia Prawnicze / The Legal Studies, 2010)
Techniki eksperymentalne, w tym testy dyskryminacyjne, mające na celu wykazanie zachowań dyskryminacyjnych, zaczęto stosować w latach 60. i 70. w Stanach Zjednoczonych i Wielkiej Brytanii, początkowo głównie w obszarze wynajmu mieszkań oraz zatrudnienia. Testy przeprowadzane były przez instytucje publiczne, pracowników naukowych i aktywistów. Zaawansowane badania w przedmiocie testów dyskryminacji ze względu na rasę i pochodzenie etniczne prowadziła także w latach 90. Międzynarodowa Organizacja Pracy. Z biegiem czasu na kontynencie europejskim badacze oraz prawnicy zaczęli akceptować i stosować metodę situation testing. Wykorzystywano je także w pracy organizacji pozarządowych, instytucji państwowych i sądów. Jednak pomimo wielu lat doświadczenia w państwach anglosaskich i szeregu pogłębionych badań naukowych, dopuszczalność stosowania tego typu dowodów w postępowaniu sądowym wciąż wzbudza wątpliwości, a nawet kontrowersje.W Polsce metoda ta jest praktycznie nieznana i niewykorzystywana. Wydaje się, że poza wąskim gronem specjalistów, zajmujących się prawem antydyskryminacyjnym, ani sądy, ani instytucje państwowe (także te powołane do przeciwdziałania dyskryminacji) o testach dyskryminacynych nigdy nie słyszały i nie wykazują zainteresowania tematem. Warto zatem przyjrzeć się, jak inne kraje Unii Europejskiej uregulowały w swoich systemach prawnych możliwość wykorzystania wyników testów dyskryminacyjnych jako dowodów w procesie sądowym, aby następnie przeanalizować pod tym kątem polskie przepisy prawne. The article presents an issue of using the results of situation testing in discrimination cases. It consists of two main parts: the first one describes experience of other EU countries in conducting situation testings and using their results in lawsuits. The second one is an analysis of Polish legal regulations in this respect. Situation testing is an experimental technique aiming at proving discriminatory behaviours. It has been developed and conducted in the United States and the United Kingdom from the 1960s, initially in housing and employment sector. Later on it has been adopted in certain European Union states. According to the method, pairs (e.g. of applicants for accommodation or a job vacancy, clients of a restaurant, a nightclub etc.) are established in such a way that they differ solely on the basis of a single characteristic reflecting the discriminatory ground (gender, ethnicity, age, disability, religion or belief, sexual orientation) under scrutiny. If one person in the pair faces different treatment, the distinction points to discriminatory behaviour. Regardless of long-term experience of the Anglo-Saxon countries and multiple scientific researches, a possibility to use this method and present its result in the court remains doubtful, if not controversial. In Poland the issue of situation testing is hardly known, even among experts dealing with anti-discrimination law, judges or public institutions competent for counteracting discrimination. First of all, one should make a distinction between experimental tests used for scientific purposes and for individual case. As far as the scientific test is concerned, its results do not necessary serve proving concrete discrimination case, however they may support the claim as statistic data making fact of discriminatory behaviour more probable. The situation testings conducted for the only purpose of trial are something different and it is not so evident whether their result may be accepted as a legal proof. Within the European Union situation testings have been conducted in Belgium, Bulgaria, Czech Republic, Denmark, Finland, France, the Netherlands, Slovakia, Sweden, Hungary and Latvia. France, Hungary and Belgium are examples of the countries where using their results as evidences is regulated directly by the law. But even over there it has been problematic and posed a lot of questions as for the legality, methodology and “moral” aspects of the technique. For instance in Belgium the issue became a subject of political debate and the right-wing parties strongly opposed to possibility of legalizing this method. Actually conducting the tests is accepted by law and Belgium courts allow to use its results. In France the method is also regulated by law (Criminal Code) and there have even been special recommendations adopted in order to clarify and explain to judges how to understand the notion of situation testing and use it in practice. In Sweden the method of testing has been for a long time problematic and treated as a provocation forbidden by law. However using its results in the courts became possible because of general legal rule of freedom of evidence applied in the proceedings. The Swedish court once even granted a compensation for discrimination to the “actors” testing discriminatory behaviour of doormen at the entrance to the night clubs, regardless their lack of status of a real victim. An interesting example of a country where the situation testing has been progressively accepted is Hungary. Not only the courts finally permitted to use the result of this method, but also it has been introduced to the legal regulations. All this happened thanks to one nongovernmental organization which made the notion of situation testings popular and consequently conducted tests proving discrimination. In Poland the method is not known, nor is it applied in practice. The law does not regulate the possibility to use the results of such a testing as evidence in discrimination cases. Moreover until recently it was difficult to suit a person for unequal treatment in the areas other than employment. There have also been doubts as for the rule of reversed burden of proof, since it was regulated only in the Labour Code. Since the act on equal treatment came into force it has changed. Although the Polish legal system does not provide for the possibility to use in the court the results of the experimental tests, it would not be completely unlikely to do so. First of all there is a rule of freedom of evidence and all evidences essential for the case should be taken into consideration. Secondly, a judge has also certain scope of discretion in examining presented proofs. Finally, the catalogue of possible evidences is not limited. However, it is not certain whether a judge would accept such a proof which comes from sort of “provocation” and has been obtained in a tricky way. The conclusion is that bearing in mind experience of other EU countries where acceptance of situation testing and using its results in the judicial proceedings has not come easily but finally became reality, conducting tests in Poland does not seem impossible. However certain obstacles may appear. Undoubtedly not only judges would play the important role but also lawyers-activists who are invited to conduct such a test, present in the court its results and popularize the idea of situation testing in Poland.